Leg stiffness and energy minimisation in human running gaits - Wróblewska, Z.; Kowalczyk, P.; Przednowek, K. (Sports Engineering, 2024)
A novel application of spring-loaded inverted pendulum model is proposed in this study. In particular, we use this model to find the existence of so-called fixed points, which correspond to actual running gaits, as functions of model parameters such as stiffness and energy. Applying the model to experimental data allows us to draw justifiable conclusions on mechanical energy minimisation for running gaits. The data were collected during a study witch 105 athletes. Force was measured using a pressure plate integrated in a treadmill. Kinematic data were recorded using two high-speed video cameras and an accelerometer placed on the back sacral localization. Each athlete completed trials by running at four different targeted velocities (9, 12.5, 16, 19.5 km/h). Running velocity influenced the values of the leg spring stiffness approximations, while the values of stiffness, determined using data from the pressure plate and camera, vary only slightly. The mechanical energy corresponding to periodic running gaits was studied with leg stiffness determined from the experiment. The mechanical energy of the runner slightly exceeded the minimum value of energy required for the existence of fixed points in the model. These results contribute to the general understanding of running gaits in terms of mechanical energy optimization.